Identifying core principles for sound formative brass teaching in South Africa: A supplementary aid for emerging teachers in the formal and non-formal sector - Geldenhuys, Lara (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMus)--Stellenbosch University, 2024.